New Insight Into the Cardioprotective Effects of Allium ursinum L. Extract Against Myocardial Ischemia-Reperfusion Injury - Rankovic, Marina; Krivokapic, Milos; Bradic, Jovana; Petkovic, Anica; Zivkovic, Vladimir; Sretenovic, Jasmina; Jeremic, Nevena; Bolevich, Sergey; Kartashova, Maria; Jeremic, Jovana; Bolevich, Stefani; Jakovljevic, Vladimir; et al. (Frontiers in Physiology, 2021)
The aim of this study was to estimate the effects of increasing doses of A. ursinum methanol extract on cardiac ischemia/reperfusion injury (I/R) with a special emphasis on the role of oxidative stress. Fifty rats were randomly divided into five groups (ten animals per group) depending on the applied treatment as follows: sham – rats who drank only tap water for 28 days and hearts were retrogradely perfused for 80 minutes without I/R injury; I/R- rats who drank only tap water for 28 days and hearts were exposed to ex vivo I/R injury and rats who consumed increasing doses of A. ursinum 125 mg/kg, 250 mg/kg and 500 mg/kg for 28 days before I/R injury.. Hearts from all rats were isolated and retrogradely perfused according to Langendorff technique. Parameters of oxidative stress were spectrophotometrically measured in blood, coronary venous effluent and heart tissue. Intake of wild garlic extract for 28 days significantly contributed to the recovery of cardiac function, which was reflected through preserved cardiac contractility, systolic function and coronary vasodilatory response after ischemia. Also, wild garlic extract showed the potential to modulate the systemic redox balance and stood out as a powerful antioxidant. The highest dose led to the most efficient decrease in cardiac oxidative stress and improve recovery of myocardial function after I/R injury. We might conclude that wild garlic possesses a significant role in cardioprotection and strong antioxidant activity, which implicates the possibility of its use alone in prevention or as adjuvant antioxidant therapy in cardiovascular diseases.